Upaya Penanggulangan Kejahatan Perdagangan Orang Bagi Pekerja Migran Indonesia - Ahmad Irzal Fardiansyah; Fristia Berdian Tamza; Nurul Mutiara Aisyah (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
The condition of a country experiencing an economic crisis can have a very broad impact on the country, one of which is the lack of domestic employment opportunities, resulting in an increase in the number of unemployed people, which leads to the goverment’s helplessness to overcome poverty. This causes citizens to flock to work abroad. The handling must be balanced with cooperation with several parties, not only the government, and implementers of labor placement but also to prospective workers so that legal problems do not arise between workers and those who provide work. This study aims to analyze efforts to overcome the crime of trafficking in persons for Indonesian migrant workers. This research uses normative juridical and empirical juridical approaches to understand the obstacles and challenges in handling human trafficking cases.